Architecture as a Symbol of Social-Economic Relationship at Al Munawar Village in Palembang - Johannes Adiyanto; Listen Prima; Muhammad Fajri Romdhoni (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Palembang is a city with a long history and one of the oldest cities in Indonesia. One of the driving aspects for the formation of the city is its reputation as the area for main trade in Southern Sumatra. The trade also encouraged the development of immigrant communities which later became their inhabited colonies such as the Al-Munawar Village inhabited by immigrants from Yemeni Arabs. The primary goal of this research is to demonstrate the impact of trade interactions on architectural expression. This demonstrates that architectural form is impacted by a variety of factors, namely commercial interactions. Therefore, this research was conducted to determine the correlation between the history of a community and its architectural elements ranging from regional spatial planning to decorative elements. This involved using the historical research approach with architectural semiotic analysis techniques. The results showed that the spatial layout of Al-Munawar Village has a typology similar to those in settlers' villages, for both fellow Yemeni Arabs in Sungai Lumpur Village and Chinese migrants in Kapitan Village. It was also discovered that the buildings in Al- Munawar Village reflect the relationship between the residents and the surrounding environment as observed with the Sultanate of Palembang Darussalam. The buildings also reflect the relationship with Yemeni Arab migrants outside Indonesia such as those in Malaysia and Singapore. This means architecture is used as a sign of the socio- economic relations for the residents of Al-Munawar village.